HoBi-Like Pestivirus and Reproductive Disorders - Decaro, Nicola (Frontiers in Veterinary Science, 2020)
HoBi-like pestivirus (HoBiPeV) is an emerging group of pestiviruses that has been detected in cattle and other ruminants in South America, Europe, and Asia. Analogous to other bovine pestiviruses, namely bovine viral diarrhea (BVDV) 1 and 2, HoBiPeV is able to cause a variety of clinical forms that range from asymptomatic infections to fatal disease, having a great impact on cattle productions and causing substantial economic losses, mainly as a consequence of the occurrence of reproductive failures. The manuscript aims to provide an updated review of the currently available literature about the impact of HoBiPeV infection on cattle reproduction. The reproductive disorders observed in cattle due to natural and experimental infections caused by this virus are reported along with the few available in-vitro studies involving the reproductive tract. HoBiPeV should be considered among the bovine pathogens that impact on reproduction, but there is a need for more specific and sensitive diagnostic methods, while the cross-protection elicited by commercially available BVDV vaccines should be better investigated.